Financial Inclusion and Macroeconomic Stability in South Africa - Matsebula, Velenkosini; Sheefeni, Johannes (International Journal of Economics and Financial Issues, 2022)
While Financial inclusion has been largely considered to play an important role to eradicate poverty and boost economic prosperity, some empirical literature has shown differing sentiments, suggesting that vast access to finance may potentially bring about market instability to the economy. This relationship between financial inclusion and macroeconomic stability is in greatly under researched, from a global and local perspective. This paper utilizes a VAR model to analyse the relationship between financial inclusion and macroeconomic stability in South Africa, using quarterly time series data from 2004 to 2019. To measure macroeconomic stability, the study used two macroeconomic factors, namely output and inflation, and commercial bank branches per 100,000 adults (CBB) was used as a measure of financial inclusion. The results find a positive relationship between financial inclusion and output, a 1% increase in CBB causes output to increase by 0.04%. Financial inclusion is also found to have a positive impact on inflation in the long run. Important policy implications point to the importance of financial inclusion in impacting output, and the need to find a balance between financial inclusion and inflation control. As such, Macroeconomic policy maker can use financial inclusion as a tool to retain macroeconomic stability.